AI In Nigerian Elections: Tool for Safeguarding Democracy or Weapon for Deepfakes and Disinformation - Okezie, Wisdom Iheanyichukwu; Inobemhe, Kelvin; Udeh, Nick-Tansi Saint; Modeyin, Oluwatobi Enitan (Nepal Journal of Multidisciplinary Research, 2025)
Background: The pervasive rise of deepfakes and disinformation poses a profound threat to democratic institutions, especially during electoral processes. In Nigeria, where electoral integrity is frequently undermined by misinformation and politically motivated propaganda, the integration of Artificial Intelligence (AI) presents a viable frontier for safeguarding democratic values. Purpose: This study was conducted to investigate the multifaceted role of AI technologies in combating the dissemination of deepfakes and disinformation during Nigerian elections, and also enhancing the spread of these malicious media contents. Methods: The systematic literature review was adopted by the researchers to draw lessons from existing literature and analyse same to find patterns that meet the research objectives. This was also to draw lessons from the past general elections in Nigeria considering relevant literature, case studies, and theoretical models. Results: This study’s results show the role AI played in aiding and fighting disinformation and deep fake, and how the country can leverage on this to improve future elections as preparations are on toward the conduct of the 2027 election. The study also shows that while AI holds considerable promise in identifying and mitigating false information, its success is largely on the role of fact checking organisations who have invested so much resource in combating the menace to improve the integrity and credibility of elections. Conclusion: The researchers conclude by proposing workable and practicable solutions that if applied by electoral institutions and stakeholders would go a long way in ensuring a sustained and healthy political climate during elections Novelty: Taking a cue from existing literature, this study provides insights as to ways the challenge of deepfakes can be tackled in Nigeria.